Motor Activity in the Informational Environment of High-School-Age Students - Andriy Mandyuk; Marta Yaroshyk; Olha Rymar (Фізичне виховання, спорт і культура здоров’я у сучасному суспільстві, 2018)
The goal of the research is to reveal the main sources of information on motor activity that affect the information environment of high-school-age students. Tasks of the study: find out the frequency of obtaining the information about motor activity by high-school-age students; reveal the main sources from which the information about the motor activity is received by high-school-age students. The survey was conducted among students of the 10th-11th forms of secondary schools in Lviv, Ternopil, Ivano-Frankivsk and Khmelnytsky. The total number of students was 925 (450 boys and 475 girls). The frequency of receiving information on motor activity by 15–17-year-old students of secondary schools was determined. The main sources which provide high–school–age students with the information on the motor activity were revealed. The purpose of using one or another source of information by students of the 10th–11th forms was identified. The peculiarities of television and Internet content, which forms the information space of high-school-age students, are determined. The obtained results showed that the main amount of information that comes to students is entertaining one. The main sources of information about the motor activity for high-school-age students are the Internet, friends and peers. The survey data are interpreted taking into account the gender particularities of students.